1987
DOI: 10.1002/neu.480180303
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the heparan sulfate proteoglycans from the extracellular matrix of rat skeletal muscle

Abstract: We have previously shown that asymmetric collagen-tailed acetylcholinesterase (AChE) is anchored to the extracellular matrix (ECM) by heparan sulfate proteoglycans (HSPGs). Here we present our studies on the characterization of such PGs from the ECM of rat skeletal muscles. After radiolabeling with 35SO4 for 24h, PGs were extracted from the muscle ECM with 4.0 M guanidine-HCl containing protease inhibitors. PGs were subsequently isolated using sequential DEAE-Sephacel chromatography, digestion with chondroitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 38 publications
(17 reference statements)
1
30
0
Order By: Relevance
“…Western blot analysis of proteoglycans Protein extracts were prepared with a protocol slightly modified from that previously described by Brandan and Inestrosa (Brandan and Inestrosa, 1987). Briefly, skeletal muscle was homogenized in 4 M guanidine-HCl, 0.05 M sodium acetate (pH 5.8) and 1 mM PMSF at 4°C and maintained under agitation for 18 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis of proteoglycans Protein extracts were prepared with a protocol slightly modified from that previously described by Brandan and Inestrosa (Brandan and Inestrosa, 1987). Briefly, skeletal muscle was homogenized in 4 M guanidine-HCl, 0.05 M sodium acetate (pH 5.8) and 1 mM PMSF at 4°C and maintained under agitation for 18 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Pooled intact radiolabeled proteoglycans were subjected to alkali extraction in the presence of 1.0 M NaBH 4 , as described previously (Brandan and Inestrosa, 1987) to release intact GAG chains. Core proteins were degraded by proteinase K (Sigma) treatment: 50 µg/ml of enzyme at 65°C for 1 hour, in buffer containing 50 mM Tris-HCl pH 7.4, 0.1 M NaCl and 5 mM CaCl 2 (Veiga et al, 1997).…”
Section: Biochemical Analysis Of Proteoglycans and Gagsmentioning
confidence: 99%
“…Core proteins were degraded by proteinase K (Sigma) treatment: 50 µg/ml of enzyme at 65°C for 1 hour, in buffer containing 50 mM Tris-HCl pH 7.4, 0.1 M NaCl and 5 mM CaCl 2 (Veiga et al, 1997). To determine GAG identities, samples were either treated with nitrous acid to specifically hydrolyze heparan sulfate chains, as described by (Brandan and Inestrosa, 1987), or incubated with 50 mU chondroitinase ABC (Seikagaku, Japan) for 18 hours at 37°C to hydrolyze chondroitin/dermatan sulfate chains (Riquelme et al, 2001). …”
Section: Biochemical Analysis Of Proteoglycans and Gagsmentioning
confidence: 99%
“…It is still a matter of discussion if the collagen subunit of this enzyme interacts with laminin or other components of basement membranes. Vigny et al (1983) as well as Brandan & Inestrosa (1987) demonstrated that the asymmetrical form of acetylcholinesterase binds to heparin sulphate proteoglycan and to a lesser extent to laminin and fibronectin contained in the basal lamina present at the neuromuscular junction. However, Grassi et al (1983) were not able to find any binding of the enzyme to basement membrane components.…”
Section: Discussionmentioning
confidence: 99%